Cost-effectiveness analysis of the adjunctive therapy of ivabradine for the treatment of heart failure with reduced ejection fraction - Rungroj Krittayaphong (2020)
© 2019 Krittayaphong et al. Background: The benefit of ivabradine as an adjunctive therapy to conventional treatment in patients with heart failure (HF) with reduced ejection fraction (HFrEF) is a reduction in both cardiovascular death and HF hospitalization. This study aimed to analyze the cost-effectiveness of ivabradine plus standard treatment compared with standard treatment alone. Methods and results: An analytical decision model was used to analyze lifetime costs and quality-adjusted life-years (QALYs) from a healthcare perspective. The study cohort comprised HFrEF patients with left ventricular ejection fraction (LVEF) <35%, with subgroup analysis of those with baseline heart rate ≥77 bpm. Clinical inputs were obtained from a landmark trial. All cost-related data, risk of non-cardiovascular death and readmission rate were based on Thai data. Costs and QALYs were discounted at 3% and presented as 2018 values. Findings were reported as incremental cost-effectiveness ratios (ICERs). Sensitivity analyses were also performed. Ivabradine plus standard treatment costs more than standard treatment (71,071 vs 18,736 THB or 2,161.54 vs 569.82 USD), and is more effective (6.08 QALYs vs 5.84 QALYs), yielding an ICER of 214,219 THB/QALY (6,515.16 USD/QALY). Ivabradine was not cost-effective at the Thai willingness to pay threshold of 160,000 THB/ QALY. The results were sensitive to risk of non-hospitalization cardiovascular death, and costs of HF hospitalization and ivabradine. However, the ICER of subgroup was below the threshold (86,317 THB/QALY or 2,625.20 USD/QALY). Conclusion: This study revealed the addition of ivabradine to standard treatment to be a cost-effective treatment strategy in HFrEF patients with a heart rate ≥77 bpm.